Neurobiology of Anorexia and Bulimia Nervosa - Kaye, Walter (Physiology & behavior, 2008)
Anorexia nervosa (AN) and bulimia nervosa (BN) are related disorders of unknown etiology that most commonly begin during adolescence in women. AN and BN have unique and puzzling symptoms, such as restricted eating or binge-purge behaviors, body image distortions, denial of emaciation, and resistance to treatment. These are often chronic and relapsing disorders, and AN has the highest death rate of any psychiatric disorder. The lack of understanding of the pathogenesis of this illness has hindered the development of effective interventions, particularly for AN. Individuals with AN and BN are consistently characterized by perfectionism, obsessive–compulsiveness, and dysphoric mood. Individuals with AN tend to have high constraint, constriction of affect and emotional expressiveness, ahendonia and asceticism, whereas individuals with BN tend to be more impulsive and sensation seeking. Such symptoms often begin in childhood, before the onset of an eating disorder, and persist after recovery, suggesting they are traits that create a vulnerability for developing an ED. There is growing acknowledgement that neurobiological vulnerabilities make a substantial contribution to the pathogenesis of AN and BN. Considerable evidence suggests that altered brain serotonin (5-HT) function contributes to dysregulation of appetite, mood, and impulse control in AN and BN. Brain imaging studies, using 5-HT specific ligands, show that disturbances of 5-HT function occur when people are ill, and persist after recovery from AN and BN. It is possible that a trait-related disturbance of 5-HT neuronal modulation predates the onset of AN and contributes to premorbid symptoms of anxiety, obsessionality, and inhibition. This dysphoric temperament may involve an inherent dysregulation of emotional and reward pathways which also mediate the hedonic aspects of feeding, thus making these individuals vulnerable to disturbed appetitive behaviors. Restricting food intake may become powerfully reinforcing because it provides a temporary respite from dysphoric mood. Several factors may act on these vulnerabilities to cause AN to start in adolescence. First, puberty-related female gonadal steroids or age-related changes may exacerbate 5-HT dysregulation. Second, stress and/or cultural and societal pressures may contribute by increasing anxious and obsessional temperament. Individuals with AN may discover that reduced dietary intake, by reducing plasma tryptophan availability, is a means by which they can modulate brain 5-HT functional activity and anxious mood. People with AN enter a vicious cycle which accounts for the chronicity of this disorder because caloric restriction results in a brief respite from dysphoric mood. However, malnutrition and weight loss, in turn, produce alterations in many neuropeptides and monoamine function, perhaps in the service of conserving energy, but which also exaggerates dysphoric mood. In summary, this article reviews findings in brain chemistry and neuroimaging that shed new light on understanding the psychopathology of these difficult and frustrating disorders.